Nematode effector proteins: an emerging paradigm of parasitism - Mitchum, Melissa G.; Hussey, Richard S.; Baum, Thomas J.; Wang, Xiaohong; Elling, Axel A.; Wubben, Martin; Davis, Eric L. (The New phytologist, 2013)
Phytonematodes use a stylet and secreted effectors to modify host cells and ingest nutrients to support their growth and development. The molecular function of nematode effectors is currently the subject of intense investigation. In this review, we summarize our current understanding of nematode effectors, with a particular focus on proteinaceous stylet-secreted effectors of sedentary endoparasitic phytonematodes, for which a wealth of information has surfaced in the past 10 yr.Weprovide an update on the effector repertoires of several of the most economically important genera of phytonematodes and discuss current approaches to dissecting their function. Lastly, we highlight the latest breakthroughs in effector discovery that promise to shed new light on effector diversity and function across the phylum Nematoda.